KARAKTERISTIK PAPAN PARTIKEL DARI LIMBAH KULIT KACANG TANAH DENGAN PEREKAT ALAMI ASAM SITRAT DENGAN PELARUT ASAP CAIR - Agus Ngadianto; Ganis Lukmandaru; Dhuria Maulidya Sari; Utari Mardatillah; Dera Fara Fitria (Forestry Study Program University Of Mataram, 2018)
Binderlessboard is one of the potential eco friendly products that can be developed. Utiliation of natural adhesives for non-wood composite is still very limited. Therefore, this research is focused on effects of citric acid content and pressing time on characteristics of particleboard made from peanut shell including its durability to dry wood termite attacks. Peanut shell particles were used as raw materials. Citric acid dissolved in liquid smoke which functioned as a water substitute solvent under a certain ratio and the concentration of the solution was adjusted to 60%. The use of liquid smoke is expected to increase the durability of the particleboard. Factors used in this research were citric acid content (10-30% based on dry weight particles) and pressing time (10 minutes and 15 minutes). Properties of particleboard were analyed based on Japanese Industrial Standard (JIS) A 5908 for particleboard. The dry wood termite resistance was then analyzed for its weight loss and mortality after 4 weeks. The results showed that the best particleboard was obtained from the treatment of 30% citric acid content with 15 minutes of pressing time where only the modulus of rupture and modulus of elasticity did not met the requirement of JIS A 5908 type 8 with the thickness swelling were 3.276%, water absorption were 44,991%, internal bonding were 4.679 kgf / cm², modulus of rupture were 26.822 kgf / cm², and modulus of elasticity were 8,986,058 kgf / cm². The best value of weight loss and mortality of dry wood termites on particleboard was obtained in a combination of 30% citric acid content with 10 minutes pressing time were 1.083% and 38.67% respectively.